Customization of information on adverse drug reactions according to patients’ needs: a qualitative study - Kusch, Marcel; Haefeli, Walter E.; Seidling, Hanna (Patient education and counseling, 2021)
Objectives - Interviewing patients, we evaluated how information on adverse drug reactions (ADRs) could be customized to best meet the patients’ expectations. - Methods - Recruitment followed an approach of variation sampling. Data collection was paper-based (questionnaires) and through semi-structured interviews. Participants were asked to evaluate different ADR characteristics (e.g. frequency, seriousness, lay perceptibility, and management strategies) as suitable filters to customize information and subsequently how they would apply these to meet their information wishes. Their wishes were then verified by presenting them accordingly customized information. - Results - Forty-one participants (mean age 44.9 ± 20.1 years) were recruited. Overall, information needs were highly diverse. Therefore, it was not possible to identify one single characteristic that was generally considered suitable. Initially, participants often wished for a maximum of information (e.g. ‘all’ ADRs). The actual presentation of comprehensive information often surprised the recipients and consequently changed the desired information. - Conclusions - By simply supplying patients with ADR information they request, it is not possible to guarantee their satisfaction with such information and their understanding of it; initial wishes might be uttered without actually comprehending their practical meaning. - Practice Implications - It is crucial to precisely assess, question, and verify information wishes in order to customize ADR information successfully.